Endoplasmic reticulum is the sorting core facility in the Golgi-lacking protozoan Giardia lamblia - Zamponi, Nahuel (2017)
Our understanding of protein and lipid trafficking in eukaryotic cells has been challenged by the finding of different forms of compartmentalization and cargo processing in protozoan parasites. Here, we show that, in the absence of a Golgi compartment in Giardia, proteins destined for secretion are directly sorted and packaged at specialized ER regions enriched in COPII coatomer complexes and ceramide. We also demonstrated that ER-resident proteins are retained at the ER by the action of a KDEL receptor, which, in contrast to other eukaryotic KDEL receptors, showed no interorganellar dynamic but instead acts specifically at the limit of the ER membrane. Our study suggests that the ER-exit sites and the perinuclear ER-membranes are capable of performing protein-sorting functions. In our view, the description presented here suggests that Giardia adaptation represents an extreme example of reductive evolution without loss of function.